Electrochemical behavior of dye-linked L-proline dehydrogenase on glassy carbon electrodes modified by multi-walled carbon nanotubes - Zheng, Haitao; Lin, Leyi; Okezaki, Yosuke; Kawakami, Ryushi; Sakuraba, Haruhiko; Ohshima, Toshihisa; Takagi, Keiichi; Suye, Shin-ichiro (Beilstein Journal of Nanotechnology, 2010)
A glassy carbon electrode (GC) was modified by multi-walled carbon nanotubes (MWCNTs). The modified electrode showed a pair of redox peaks that resulted from the oxygen-containing functional groups on the nanotube surface. A recombinant thermostable dye-linked L-proline dehydrogenase (L-proDH) from hyperthermophilic archaeon (Thermococcus profundus) was further immobilized by physical adsorption. The modified electrode (GC/MWCNTs/L-proDH) exhibited an electrocatalytic signal for L-proline compared to bare GC, GC/L-proDH and GC/MWCNTs electrodes, which suggested that the presence of MWCNTs efficiently enhances electron transfer between the active site of enzyme and electrode surface. The immobilized L-proDH showed a typical Michaelis–Menten catalytic response with lower apparent constant.
Keywords: dye-linked L-proline dehydrogenase; electrocatalysis; electron transfer; multi-walled carbon nanotube